The “Neglected” and the “Unexpected” in Radiotherapy-Induced Cardiotoxicity-Insights from a Monocentric Study on Myocardial Perfusion Imaging in Early Breast Cancer Patients - Gallucci, Giuseppina; Capobianco, Alba; Sisti, Leuconoe Grazia; D’Andrea, Barbara; Lapadula, Loredana; Tucciariello, Maria Teresa; Tartarone, Alfredo; Sanseverino, Francesca; Storto, Giovanni; Antonio, (Cardiology and Cardiovascular Medicine, 2020)
Background: Radiotherapy (RT) for early breast cancer (EBC) increases the subsequent rate of ischemic heart disease (IHD), often with the genderspecific microvascular phenotype. The goal of our study was to analyze the potential value of a baseline myocardial perfusion imaging (MPI) and a proactive monitoring on RT cardiotoxicity in early breast cancer patients. Methods: 70 EBC patients with an indication for RT, had a baseline stress/rest MPI, in 25 patients Coronary Flow Reserve (CFR) was also estimated. All patients received a 3-dimensional conformal RT with an average mean heart dose of 3.29 Gy. A 20-year cardiology follow-up was scheduled. Results: At baseline 12/70 patients showed MPI abnormalities; 11/12 had IHD risk factors (RF). 21/70 patients with chest pain after RT performed post-RT MPI: 7 patients showed “de novo” abnormalities, 3 increased their pre-RT abnormalities. 90% of patients with MPI abnormalities showed angiographically normal epicardial coronary arteries. 90% of patients with MPI abnormalities had risk factors for IHD, including pregnancy-related hypertension. One patient with no RF for IHD and normal baseline MPI reported post-RT abnormalities likely due to a genetic predisposition. No major cardiologic events were recorded in a 9-year follow-up in patients with baseline MPI abnormalities. Conclusions: A baseline stress/rest MPI is useful in EBC patients with a high likelihood of IHD, MPI abnormalities call for a proactive monitoring and an aggressive treatment of IHD risk factors that may reduce the burden of IHD. A gender-oriented approach and the search for genetic predisposition smooth the way towards precision medicine.